2019
DOI: 10.21608/jabps.2019.13319.1049
|View full text |Cite
|
Sign up to set email alerts
|

Natural polyphenols target the TGF-β/caspase-3 signaling pathway in CCl4-induced liver fibrosis in rats

Abstract: Background/Aims: Liver fibrosis presents a worldwide problem. There is an increasing interest in the studying of natural compounds with free radicals scavenging capacity to protect against liver fibrosis. This study investigated the actions of resveratrol and curcumin as two natural polyphenols against CCl 4 -induced liver fibrosis. Materials and Methods: Animals were divided into four groups: Normal control group; CCl 4 only group; Res group (resveratrol + CCl 4 ); Cur group (curcumin + CCl 4 ). Serum ALT and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…Moreover, these results were augmented by histological evidence showing distorted renal and hepatic architecture and increased tissue damage in CLP rats. Our findings are in accordance with several previous reports demonstrating liver and kidney dysfunction in septic rats [12,48,49]. On the other hand, the decreased serum hepatic and renal damage markers, which was substantiated with beneficial histological findings in the silymarin-treated animals highlight its hepatorenal protective effects.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, these results were augmented by histological evidence showing distorted renal and hepatic architecture and increased tissue damage in CLP rats. Our findings are in accordance with several previous reports demonstrating liver and kidney dysfunction in septic rats [12,48,49]. On the other hand, the decreased serum hepatic and renal damage markers, which was substantiated with beneficial histological findings in the silymarin-treated animals highlight its hepatorenal protective effects.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, a more recent study suggested that the cytoprotective effects of silymarin can be attributed to normalization of lipid metabolism and preservation of mitochondrial energy production in high fat feeding-induced murine model of obesity [58]. Nevertheless, several studies illustrated the protective effects of other antioxidants such as N-acetylcysteine, resveratrol, vitamin E and curcumin on different organs following induction of sepsis [14,49,59,60].…”
Section: Discussionmentioning
confidence: 99%